The Influence of Cafe Atmosphere and Food Quality on Customer Satisfaction in Building Customer Loyalty of Masalalu Café Rawa Domba Jakarta - Dzurrotul Atsnawiyah; Mohamad Rizan; Rahmi (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2022)
This research aims to analyze the influence between cafe atmosphere and customer satisfaction, food quality and customer satisfaction, cafe atmosphere and customer loyalty, food quality and customer loyalty and between customer satisfaction and customer loyalty of Masalalu Café Rawa Domba Jakarta customers. Researcher used questionnaire form to collect data and the sample of this research is 200 respondents. For cultivate and analyze the data, researcher used SPSS version 26 and Lisrel version 8.8. The results of this research show there is a positive and significant influence between cafe atmosphere and customer satisfaction. Food quality also has a positive and significant to customer satisfaction. But cafe atmosphere and food quality have no significant influence to customer loyalty. Even though, customer satisfaction has a positive and significant influence to customer loyalty. Keywords: cafe atmosphere, food quality, customer satisfaction, customer loyalty, Masalalu Café.